ROLE OF SDF-1 AND CELECOXIB IN INCREASING QUANTITY OF NEURAL STEM CELL IN THE LESION ZONE AND OUTCOME OF SPONTANEOUS INTRACEREBRAL HEMORRHAGE - Sinurat, Robert; Maskoen, Ani Melani; Hilmanto, Dany; Wiriadisastra, Kahdar (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: We studied the effect of stromal derived factor-1 (SDF-1) and celecoxib for increasing the amount of neural stem cells in the lesion zone and clinical outcomes of spontaneous intracerebral hemorrhage. Methods: Twenty-eight rats, strain Wistar, divided into four groups: control, treated with celecoxib, SDF-1, and the combination of celecoxib+SDF-1. The neural stem cells identified by immunohistochemistry procedures with Nestin as primary antibodies and the levels of proliferation were assessed by Ki-67 as primary antibodies. The clinical outcomes were examined by Bederson scale. Results: This study revealed the combination treatment group had the highest histoscores of Nestin and highest of Ki-67 histoscores for SDF-1 group. The amount of neural stem cells in the lesion zone of treatments groups was higher than controls (p<0.005), but similar between treated groups (P>0.05). The proliferation levels were higher in SDF-1 group (P<0.05), and the clinical outcomes back to normal were highest in combination therapeutic groups, even though not different when compared to another group (p>0.05). Conclusion: The results suggest celecoxib, SDF-1, and the combination of celecoxib+SDF-1 can increase neural stem cells in spontaneous intracerebral hemorrhage, and SDF-1 increased proliferation levels. The clinical outcomes were not significantly different between rats, regardless of the fact that almost all of rats in the combination group were back to normal. Keywords: Neuroinflammation, Cyclooxygenase-2, Bederson Scale